DaVInt - Data Visualization and Interaction Lab - Manssour, Isabel H.; Silveira, Milene S. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais Estendidos da XXXIV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2021.20046, 2021)
A multidisciplinary research project between Communication and Computer Science researchers gave rise to the Data Visualization and Interaction Lab, known as DaVInt lab. Officially created in 2017, DaVInt comprises students and researchers from Communication, and Computer Science and related areas. DaVInt's main research topics are related to visual analytics of social media, narrative visualization, and data science. However, computer vision projects and other individual initiatives are also developed. Its main contributions are divided into three main areas: scientific, through our publications; technological, making the results of our researches available to the community; and student education, through which we disseminate the area beyond academia.